Oral health status in relation to socioeconomic factors among the municipal employees of Mysore city - B R Chandra Shekar; CVK Reddy (Wolters Kluwer Medknow Publications, 2011)
Aim: To assess the prevalence of dental caries, periodontal diseases, oral pre-malignant and malignant lesions in relation to socioeconomic factors among the municipal employees of Mysore city. Settings and Design: The study was cross sectional in nature. Materials and Methods: All the available employees (1187) during the study period were considered. World Health Organization (WHO) Oral Health Assessment form (1997) and a preformed questionnaire were used to collect the required data. Modified Kuppuswamy scale with readjustment of the per capita income to suit the present levels was used for classifying the individuals into different socioeconomic status (SES) categories. Data were collected by a single, trained and calibrated examiner (dentist) using mouth mirror and community periodontal index (CPI) probe under natural daylight. Data analysis was done using SPSS windows version 10. Quantitative data were analyzed using one-way analysis of variance (ANOVA) with Tukey's post hoc test and qualitative data were analyzed using chi-square or contingency coefficient. Results: The age range of the study population was 19-57 years (mean 40.74 years, standard deviation 9.17). The prevalence of dental caries in the upper SES category was lesser (43.3%) compared to that in lower SES category (78.6%). 16.4% of the subjects in the upper category had a CPI score of 0 (healthy periodontium) and none of the subjects in the lower middle, upper lower and lower SES category had this score. The prevalence of oral pre-malignant and malignant lesions was higher in lower SES category (17.9%) than in upper class (0%). Conclusion: There was an inverse relationship between oral health status and SES. The overall treatment need was more in the lower class people than in the upper class.